Effect of Superheat on the Performance of CO2 Micro-channel Evaporator - Yu Binbin; Wang Dandong; Chen Jiangping (Zhileng xuebao)
As a natural refrigerant, CO2 has received increasing attention from the international community, particularly in the European market, and domestic demand is also increasing. This study analyzes the key factors influencing the cooling capacity of a CO2 micro-channel evaporator, where a CO2 micro-channel evaporator test bench was built and a superheat adjustment was realized using the CO2 electronic expansion valve. The results show that the CO2 superheat has a greater effect on the cooling capacity of the evaporator than other refrigerants, and the evaporator capacity is considerably improved with a decrease in superheat, the rate of increase can be categorized into three obvious periods with different characteristics. The increase in evaporator capacity described in this study can reach up to 57.9%. In addition, thermocouples and infrared thermal imaging were used to obtain the distribution of outlet air temperatures, where the outlet air temperatures achieve better uniformity with a decrease in superheat.